HUBUNGAN TINGKAT PENGETAHUAN SUNSCREEN DENGAN PERILAKU PENGGUNAAN SUNSCREEN PADA REMAJA SISWI KELAS XI DI SMA N 1 CAWAS - Normaningtyas Auliadini; Endang Setyowati; Fahrudin Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Exposure to ultraviolet (UV) radiation can cause various harmful effects in humans, one of which is skin cancer. The use of sunscreen can help reflect UV radiation; however, public knowledge regarding the dangers of UV radiation and the benefits of sunscreen remains limited. This study aimed to determine the relationship between the level of sunscreen knowledge and sunscreen use behavior among female students of SMA N 1 Cawas. This study employed a quantitative correlational method with a cross-sectional approach. A total of 94 respondents were selected using purposive sampling. The study was conducted from July 2025 to February 2026 using a questionnaire consisting of 6 knowledge questions and 8 behavior questions. Data analysis included univariate and bivariate analysis. The results showed that all respondents were female, with the majority aged 16 years (61.70%). The most commonly used sunscreen was cream (69.14%), most respondents used SPF ≥30 (91.48%), applied sunscreen using ≥2 finger lengths (56.38%), and had used sunscreen for ≥1 year (81.91%). Most respondents had a good level of knowledge (57.45%) and good sunscreen use behavior (53.19%). Correlation test results showed no significant relationship between the level of sunscreen knowledge and sunscreen use behavior (r = 0.122; p = 0.494). It can be concluded that there was no significant relationship between sunscreen knowledge level and sunscreen use behavior among 11th-grade female students at SMA N 1 Cawas, Klaten Regency.